The Political Cost of Being Soft on Crime: Evidence from a Natural Experiment - Francesco Drago; Roberto Galbiati; Francesco Sobbrio (Center for Economic Studies and ifo Institute (CESifo), 2017)
We provide evidence about voters' response to crime control policies. We exploit a natural experiment arising from the Italian 2006 collective pardon releasing about one third of the prison population. The pardon created idiosyncratic incentives to recidivate across released individuals and municipalities. We show that municipalities where resident pardoned individuals have a higher incentive to recidivate experienced higher recidivism. Moreover, in these municipalities: i) newspapers were more likely to report crime news involving pardoned individuals; ii) voters held worse beliefs on the incumbent governments ability to control crime and iii) with respect to the previous elections, the incumbent national government experienced a worse electoral performance in the April 2008 national elections relative to the opposition coalition. Overall, our findings indicate that voters keep incumbent politicians accountable by conditioning their vote on the observed effects of their policies.
Keywords: D72; K42; 330; accountability; voting; natural experiment; crime; recidivism